Developing the Professional Workforce for Adult Literacy Education. Policy Brief - Lytle, Susan L.; National Center on Adult Literacy, Philadelphia, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
Poor preparation of adult literacy educators is often blamed for the failure of adult literacy students. Four critical issues related to developing the adult literacy professional work force are as follows: how literacy is learned in adulthood; how practitioners learn and improve their practice; how new knowledge is generated in and for the field; and how a professionalized work force can play a role in curriculum development. The Adult Literacy Practitioner Inquiry Project is designed to investigate inquiry-centered staff development as a promising direction for rethinking practice and research and for generating knowledge from a field-based perspective. Its core activity is an ongoing research seminar for practitioners. Participants conduct systematic, intentional inquiry into teaching, learning, and administration in their own program settings. Preliminary findings from participant interviews show that adult literacy educators have extensive prior knowledge and experience and have had a variety of experiences with research and development. Many feel they are more or less on their own or that professional supervision is unhelpful. Opportunities to learn on the job are constrained by demoralizing physical conditions and time pressures. They come to staff development with a range of concerns more complex than those typically dealt with. Effective staff development should use practitioners' prior knowledge and experience, start from practitioner questions, and generate new knowledge for the field. (Contains 28 references.) (YLB)
Sponsoring Agency: Department of Health and Human Services, Washington, DC.
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Sponsoring Agency: Department of Labor, Washington, DC.
Contract Number: R117Q00003.
ERIC Note: Paper presented at the Literacy Policy Forum (Washington, DC December 18, 1992). For a related document, see CE 063 229.
May also be available online. Address as at 14/8/18
Keywords: Adult Basic Education; Adult Educators; Adult Literacy; Educational Research; Information Seeking; Inquiry; Learning Processes; Learning Strategies; Literacy Education; Models; Professional Development; Research Methodology; Staff Development; Teacher Researchers; Theory Practice Relationship; Reports, Research; Speeches/Meeting Papers